2021
DOI: 10.1088/1361-6528/ac2d0a
|View full text |Cite
|
Sign up to set email alerts
|

Highly transparent and conductive p-type CuI films by optimized solid-iodination at room temperature

Abstract: p-type CuI films with optimized optoelectronic performance were synthesized by solid-phase iodination of Cu3N precursor films at room temperature. The effects of the deposition power of Cu3N precursors on the structural, electrical, and optical properties of the CuI films were systematically investigated. X-ray diffraction results show that all the CuI films possess a zinc-blende structure. When the deposition power of Cu3N precursors was 140 W, the CuI films present a high transmittance above 84% in the visib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…In this work, for the stabilized and optimized -CuI thin film whereas T = 65 %, R s = 210 4 , resulting in a Haacke's FOM equal to 6.710 -7  -1 . This FOM is similar to that of other p-type TCO materials 4,66,67 , and similar 58 or even lower 13,59,68 than that of other -CuI thin films. This difference can be explained by the fact that, in this work, the thin films were not prepared in an iodine rich environment, causing a limited number of Cu vacancies which is beneficial for p-type electrical conduction.…”
Section: Figure Of Meritsupporting
confidence: 83%
“…In this work, for the stabilized and optimized -CuI thin film whereas T = 65 %, R s = 210 4 , resulting in a Haacke's FOM equal to 6.710 -7  -1 . This FOM is similar to that of other p-type TCO materials 4,66,67 , and similar 58 or even lower 13,59,68 than that of other -CuI thin films. This difference can be explained by the fact that, in this work, the thin films were not prepared in an iodine rich environment, causing a limited number of Cu vacancies which is beneficial for p-type electrical conduction.…”
Section: Figure Of Meritsupporting
confidence: 83%
“…The formation of a built-in electric field reduces the recombination of electrons and holes, increasing the concentration of photogenerated carriers. Figure 14 is a comparison of this work and other heterojunctions [18,22,25,[41][42][43]. As can be seen from the figures, the ideality factor of our heterojunction is better than others, proving that it is of high quality with fewer defects.…”
Section: Resultsmentioning
confidence: 79%
“…These techniques have good film-forming characteristics, making them ideal for research. Furthermore, it has been shown that the quality of the precursor significantly affects the transmittance of CuI [18]. The high-power impulse magnetron sputtering (HiPIMS) is preferred for preparing precursors due to its higher particle dissociation rate, resulting in a denser film surface that impacts the optoelectronic properties of the film [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Corrosion protection usually use surface modification technology to change the chemical composition or organizational structure of the material surface in order to improve the material performance to effectively improve the work stability of the workpiece and service life, such as corrosion resistance, anti-wear, photoelectric properties, etc [7][8][9]. Common surface modification techniques mainly include chemical heat treatment, ion implantation, thermal spray coating technology, physical vapor deposition hard coating, laser cladding and so on.…”
Section: Introductionmentioning
confidence: 99%